Muscle Channelopathies: the Nondystrophic Myotonias and Periodic Paralyses - Statland, Jeffrey M. (Continuum (Minneap Minn), 2013)
PURPOSE OF REVIEW: The muscle channelopathies are a group of rare inherited diseases caused by mutations in muscle ion channels. Mutations cause an increase or decrease in muscle membrane excitability, leading to a spectrum of related clinical disorders: the nondystrophic myotonias are characterized by delayed relaxation after muscle contraction, causing muscle stiffness and pain; the periodic paralyses are characterized by episodes of flaccid muscle paralysis. This review describes the clinical characteristics, molecular pathogenesis, and treatments of the nondystrophic myotonias and periodic paralyses. RECENT FINDINGS: Advances have been made in both the treatment and our understanding of the molecular pathophysiology of muscle channelopathies: (1) a recent controlled trial showed that mexiletine was effective for reducing symptoms and signs of myotonia in nondystrophic myotonia; (2) the mechanisms by which hypokalemic periodic paralysis leads to a depolarized but unexcitable sarcolemma membrane have been traced to a novel gating pore current; and (3) an association was demonstrated between mutations in a potassium inward rectifier and patients with thyrotoxic periodic paralysis. SUMMARY: The muscle channelopathies are an expanding group of muscle diseases caused by mutations in sodium, chloride, potassium, and calcium ion channels that result in increased or decreased muscle membrane excitability. Recognizing patients with channelopathies and confirming the diagnosis is important, as treatment and management strategies differ based on mutation and clinical phenotype.